1998
DOI: 10.1080/02626669809492154
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of soil water movement as inferred from 18O stable isotope studies

Abstract: The seasonal movement of soil water through a deep vadose zone of a sandy hill was studied in the central part of The Netherlands. The behaviour of soil water was tracked by monitoring soil water fluctuations and changes in the environmental tracer lS 0 in vertical profiles at test sites with grassland, heathland and forest. In the temperate climate of the study area a soil moisture deficit develops during summer and a precipitation surplus prevails during winter. The 18 0 content in precipitation exhibits a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 12 publications
1
58
0
Order By: Relevance
“…This is an indication of a weak isotopic enrichment of some pore water samples. Since soil evaporation is dependent on atmospheric boundary conditions and soil characteristics (Gonfiantini et al, 1998) the ob- served enrichment of heavy isotopes may have occurred by evaporation of soil water in the uppermost soil layers. Most care was taken to avoid kinetic fractionation during sampling and transport, still a weak secondary enrichment cannot be strictly excluded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an indication of a weak isotopic enrichment of some pore water samples. Since soil evaporation is dependent on atmospheric boundary conditions and soil characteristics (Gonfiantini et al, 1998) the ob- served enrichment of heavy isotopes may have occurred by evaporation of soil water in the uppermost soil layers. Most care was taken to avoid kinetic fractionation during sampling and transport, still a weak secondary enrichment cannot be strictly excluded.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of kinetic fractionation this variability determines the atmospheric boundary condition for hydrological stable isotope studies at the plot scale. The propagation and attenuation of the seasonal isotope signal with increasing soil depth allows for an investigation of vertical water movement in the unsaturated zone at the plot scale (Zimmermann et al, 1967;Maloszewski et al, 1983;Stewart and McDonnell, 1991;Gehrels et al, 1998). Vertical stable isotope pore water profiles in the unsaturated zone have also been used to investigate recharge mechanisms and recharge rates in the vadose zone (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In nearby areas with similar climate, the maximum E occurs in May (Domingo et al, 1999). The seasonal pattern of variation in y, high in spring and late autumn and characteristically low in summer when plants actively take up soil water, is well known (Henninger et al, 1976;Ehrenfeld et al, 1997;Gehrels et al, 1998).…”
Section: Dynamics Of Water Balance Componentsmentioning
confidence: 99%
“…We assume that the net precipitation that infiltrates into the soil is not affected by isotope fractionation. A study from Gehrels et al (1998) also showed that interception will not play a significant role in isotope fractionation for lower vegetation types. Thus, the net precipitation has the same isotope signature as precipitation.…”
Section: Interceptionmentioning
confidence: 99%